2011
DOI: 10.1021/ie2017064
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a Liquid–Liquid–Solid Heterogeneous Reaction System: Model System and Peroxyvaleric Acid

Abstract: A mathematical model was developed to interpret a liquid-liquid-solid heterogeneous reaction system using valeric acid (pentanoic acid) perhydrolysis as model. Kinetic, thermodynamic and mass transfer parameters were included in this model. Perhydrolysis of valeric acid (pentanoic acid) on Amberlite IR-120 catalyst experiments were carried out in the temperature range of 40-60°C and with an initial valeric acid concentration of 50 wt.%. The influence of water and the acid catalyst was taken into account to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Based on their observation, this induction period seems to be linked to the polar effect of the aqueous phase. The concentration of protons can affect the value of the surface tension, which interferes with the interfacial area …”
Section: Resultsmentioning
confidence: 99%
“…Based on their observation, this induction period seems to be linked to the polar effect of the aqueous phase. The concentration of protons can affect the value of the surface tension, which interferes with the interfacial area …”
Section: Resultsmentioning
confidence: 99%
“…The experiments also revealed that a gelular resin with a particle size of more than 0.1 mm and 8% cross-linking degree (i.e., Amberlite IR-120) showed better resistance to deactivation. 140 To conclude, the degree of cross-linking plays a major role in the efficiency of the resins because a higher degree of cross-linking makes the reaction rate slower and the lower one can deactivate during the reaction. 141 Technological parameters such as temperature, catalyst loading, carboxylic acid to double bond ratio, hydrogen peroxide to double bond ratio, and stirring speed are optimized Table 3 Processing parameters for the epoxidation of vegetable oils using acidic ion exchange resins Table 3.…”
Section: Heterogeneous Catalytic Systemmentioning
confidence: 99%
“…By using the same methodology as described in an article of our group [23], mass transfer coefficient of peroxyformic acid in aqueous was estimated by using Calderbank and Moo-Young correlation and diffusion coefficient of peroxyformic acid in organic phase was estimated by using the correlation of Scheibel. The Hatta number was found to be lower than 1 so interfacial mass transfer can be assumed to be rapid.…”
Section: Mass Balance For Aqueous and Organic Phasesmentioning
confidence: 99%